War in Feminist Syrian Novel (Nightmares of Beirut) - القصيري, نضال (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research aims at approaching the concept of war in feminist Syrian novel, through studying Ghada al-Samman’s masterpiece Nightmares of Beirut. al-Samman foresaw Zarqa’a al-Yamama, and envisaged what others could not see, especially those involved in the war. Throughout the novel, we are inclined to live the nightmares of civil war that broke out in Lebanon in 1975, which resulted in nothing but destruction, killing, shooting, and unnecessary death. The novelist questions the role of the writer during the war and poses questions related to that role: is there any difference between the act of writing and the act of shooting; between words and bullets? Is it possible for the educated writers to be part of the crazy war, to the extent that they get involved in fighting? Or, do they fight in their own way, using their pens as weapons, their words as bullets, and, in the process, create miracles?